2015
DOI: 10.1002/jbm.a.35565
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle tissue engineering in crosslinked electrospun gelatin scaffolds

Abstract: Crosslinked, multi-layer electrospun gelatin fiber scaffolds with generally ±45 degree fiber orientation have been used to grow human umbilical vein smooth muscle cells (HUVSMCs) to create a vascular tunica media graft. Scaffolds of different fiber diameter (2-5 μm in wet state), pore size, and porosity (16-21% in wet state) were assessed in terms of cell adherence and viability, cell proliferation, and migration in both in-plane and transverse directions through the scaffold as a function of time under static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 20 publications
(41 reference statements)
1
40
0
Order By: Relevance
“…The predicted cell front propagation through the depth of the scaffold was based on the definition of the cell front at a normalized cell density (cell area fraction) of 0.5 for the cell layer attached to the fiber surface. Figure a,b, demonstrate good agreement between the predictions of this study and the experimental data by Elsayed et al (b), with the line of best fit through the predicted values after 3, 6, and 9 days of cell culture passing through the origin and crossing the experimental data for both scaffolds. Using these sets of experimental data, the cell migration coefficient in the transverse ( x ‐) and in‐plane ( y ‐) directions was fitted to the values presented in Table for a static bioreactor, and as can be seen, it was found that the migration coefficient of the SMCs is 10 times higher in the transverse direction through the fibrous scaffold than in the in‐plane direction; these values were used for all scaffolds in the validation and parametric studies in a static bioreactor in section 4.1.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The predicted cell front propagation through the depth of the scaffold was based on the definition of the cell front at a normalized cell density (cell area fraction) of 0.5 for the cell layer attached to the fiber surface. Figure a,b, demonstrate good agreement between the predictions of this study and the experimental data by Elsayed et al (b), with the line of best fit through the predicted values after 3, 6, and 9 days of cell culture passing through the origin and crossing the experimental data for both scaffolds. Using these sets of experimental data, the cell migration coefficient in the transverse ( x ‐) and in‐plane ( y ‐) directions was fitted to the values presented in Table for a static bioreactor, and as can be seen, it was found that the migration coefficient of the SMCs is 10 times higher in the transverse direction through the fibrous scaffold than in the in‐plane direction; these values were used for all scaffolds in the validation and parametric studies in a static bioreactor in section 4.1.…”
Section: Resultssupporting
confidence: 84%
“…Computational simulations of smooth muscle arterial tissue engineering were conducted for both a static and a dynamic bioreactor. In each case‐study, a first set of simulations were conducted with the aim at validating the theoretical model and fitting the values for the cell migration coefficients, D x , D y , by comparing the predictions against experimental data (Elsayed et al, a, b). The second stage of computational simulations aimed at the optimization of the microstructural parameters of the scaffold, by conducting a series of parametric studies with different values of the scaffold porosity and fiber diameter and constructing maps from which the best parameters for a scaffold would be selected on the basis of maximum cell proliferation within the shortest time, whereas the predicted oxygen concentration is above the threshold that maintains cell survival.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations